Substitution of Yellow Pumpkin Flour (Cucurbita Moschata) in Making Mille Crepes - Apipaturohmah, Pipa; Rahmawati, Yulia; Subekti, Sri (Media Pendidikan Gizi dan Kuliner, 2024)
This research aims to determine the acceptability of mille crepes products substituted with pumpkin flour, a local food with good nutritional value. Pumpkin consumption in Indonesia is low, with less than 5 kg per capita per year. Pumpkin flour is processed to extend its shelf life and can be used in various food preparations, such as mille crepes. The experimental method used includes recipe analysis, experimental trials, QDA organoleptic tests, organoleptic hedonic tests, making standard recipes, and organoleptic tests. The formulation of the research is a comparison of wheat flour and pumpkin flour for four treatments: MLCB 1, MLCB 2, MLCB 3, and MLCB 4. The QDA test results showed that the pumpkin flour substitution treatment significantly improved shape, texture, color, aroma, and taste. The MLCB 4 pumpkin flour substitution treatment was the most preferred formula. The organoleptic test results indicated that the mille crepes product substituted with pumpkin flour was positively received by consumers.